Psychological and Pedagogical Conditions for the Organization of Independent Play in Younger Preschoolers (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In the article, the author highlights the conditions for supporting independent play of children of younger preschool age, and also reveals the ideas of modern educators about the level of children's play, the features of the created developing subject-spatial environment, as well as the conditions for the transition of children to independent play.